Assessing the design thinking mindset among Islamic Senior High School students in digital technology physics topics - Indro Wicaksono; Sentot Kusairi; Parno Parno; Ahmad Taufiq (EDUSAINS, 2025)
Design thinking has emerged as a critical 21st-century competence, yet it remains under-emphasised in Islamic schools, particularly Madrasah Aliyah (Islamic senior high schools). This study investigates the design-thinking mindset of Madrasah Aliyah students studying digital-technology-based physics concepts. Employing a descriptive-correlational design, we used descriptive statistics and Pearson/Spearman correlation analyses to examine relationships among five dimensions of design thinking: (1) Growth Mindset and Endurance, (2) Empathy and Human-Centred Design, (3) Teamwork and Diverse Perspectives, (4) Creativity and Problem-Solving through Prototyping, and (5) Curiosity and Learning Motivation. Data were gathered from 136 students using a validated 25-item questionnaire. Overall mindset levels ranged from moderate to high; Curiosity and Empathy recorded the highest scores, whereas Endurance ranked lowest. Gender- and grade-level comparisons revealed that female students exhibited significantly higher Endurance. Although the cross-sectional design limited insights into developmental trends, a significant negative correlation emerged between Endurance and the other dimensions. These findings highlight the need to balance resilience with curiosity, creativity, and empathy within a design-thinking framework and offer guidance for integrating digital technologies and design-thinking principles into physics instruction while respecting the madrasah cultural context. Future research could explore the impact of interactive digital physics simulations on the development of the five design-thinking dimensions among Madrasah Aliyah students.